Transformation of Ideological Factors in New Uzbekistan, the Basis of the Development of Patriotism in Youth - Xuriyat Khudayberdiyeva (Researchparks Publishing, 2022)
In this article, the development of a national and modern outlook on spirituality in the minds of young people, to be spiritually mature and physically strong, to think deeply and to fight against various foreign ideas, to develop the minds of young people in the system of social relations with the national idea and issues such as formation with ideology, development of ideological immunity that can resist spiritual threats are covered.